Liver receptor homolog-1: structures, related diseases, and drug discovery - Wu Tong; Lu Zhi-fang; Yu Hao-nan; Wu Xi-shan; Liu Yang; Xu Yong (Acta Pharmacologica Sinica, 2024)
Liver receptor homolog-1 (LRH-1), a member of the nuclear receptor superfamily, is a ligand-regulated transcription factor that plays crucial roles in metabolism, development, and immunity. Despite being classified as an ‘orphan’ receptor due to the ongoing debate surrounding its endogenous ligands, recent researches have demonstrated that LRH-1 can be modulated by various synthetic ligands. This highlights the potential of LRH-1 as an attractive drug target for the treatment of inflammation, metabolic disorders, and cancer. In this review, we provide an overview of the structural basis, functional activities, associated diseases, and advancements in therapeutic ligand research targeting LRH-1.